Fused Deposition Modeling for Unmanned Aerial Vehicles (UAVs): A Review - Klippstein, Sven Helge; Diaz De Cerio Sanchez, Alejandro; Hassanin, Hany; Zweiri, Yahya; Seneviratne, Lakmal (Advanced Engineering Materials)
Additive Manufacturing (AM) is a game changing production technology for aerospace applications. Fused deposition modeling is one of the most widely used AM technologies and recently has gained much attention in the advancement of many products. This paper introduces an extensive review of fused deposition modeling and its application in the development of high performance unmanned aerial vehicles. The process methodology, materials, post processing, and properties of its products are discussed in details. Successful examples of using this technology for making functional, lightweight, and high endurance unmanned aerial vehicles are also highlighted. In addition, major opportunities, limitations, and outlook of fused deposition modeling are also explored. The paper shows that the emerge of fused deposition modeling as a robust technique for unmanned aerial vehicles represents a good opportunity to produce compact, strong, lightweight structures, and functional parts with embedded electronic.
Keywords: FDM; Review; UAV